Hereditary Tyrosinemia Type 1 in Jordan: A Retrospective Study - Noor A. Megdadi; Ahmad K. Almigdad; Mo'men O. Alakil; Shahrazad M. Alqiam; Sumaia G. Rababah; Moshera A. Dwiari (Hindawi Limited, 2021)
Background. Hereditary tyrosinemia type 1 (HT1) is a recessively inherited inborn error of metabolism affecting the final step of tyrosine catabolism. The accumulation of tyrosine toxic metabolites leads to progressive hepatic, renal, and neurological manifestations. Treatment of HT1 consists of tyrosine-restricted diets and nitisinone. The untreated disease progresses into life-threatening liver failure with an increased risk of hepatocellular carcinoma. Methods. From April 2010 to March 2021, eighteen patients were diagnosed with HT1 in the metabolic department at Queen Rania Al Abdullah Hospital for Children in Jordan. Patients were reviewed retrospectively regarding their clinical features, laboratory data, and sociodemographic history. Results. The mean age of nine boys and nine girls was 6.03 years (SD±3.85). The mean age for symptom onset was 5.61 months (SD±6.02). However, the diagnosis was belated from the onset by 10.50 months (±10.42). Nitisinone treatment was delayed from diagnosis around 12.28 months (SD±25.36). Most of the patients (66.7%) had acute onset of the disease. Two children (11.1%) died due to hepatic complications. Positive family history was identified in 61.1% of patients, and a similar percentage were born to parents with consanguineous marriage. The most common presentation was abdominal pain, vomiting, and fever. Hepatomegaly and abdominal distention were the most common findings. Six patients' (42.9%) first presentation was rickets. Conclusion. HT1 diagnosis is usually delayed because it is not part of newborn screening and nonfamiliarity with the clinical features of the disease. Therefore, nationwide newborn screening should be expanded to include HT1.